Georgia : First Review Under the Stand-By Arrangement-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2009)
The staff report for the First Review Under the Stand-By Arrangement with the officials of Georgia highlights economic developments and policies. Sustaining economic growth and maintaining confidence in the currency and the financial system within the constraints of available external financing are the main program priorities. IMF staff recommended a more active role for monetary policy in encouraging market interest rate adjustments. With global markets in distress, the authorities should work on contingency planning to keep the financial sector strong.